Archives Management In Improving The Quality Of Administrative Services SMP Negeri 3 Siliragung Banyuwangi - Nuryani, Siti; Al Rosid, Moh. Harun (Mudir : Jurnal Manajemen Pendidikan, 2024)
This research aims to describe the planning, implementation and evaluation of archives in improving the quality of administrative services at SMP Negeri 3 Siliragung Banyuwangi. This research approach is qualitative with a case study type of research. Data collection techniques include structured interviews, observation and documentation. Miles and Huberman model data analysis in the form of data reduction, data presentation, and drawing conclusions. The results of this research show that: (1) Planning; At this stage, planning is prepared at the end of every even semester around June for a period of two weeks through a formal meeting attended by the school principal, head of administration and administrative staff. Apart from that, also through collaboration with administrative parties. (2) Implementation; At this stage, archiving is carried out by dividing tasks according to function and responsibility, separating incoming and outgoing letters, recording all archives in the letter agenda book, assigning codes and letter numbers according to specifications. (3) Evaluation; evaluation and analysis activities through formal meetings attended by school principals, heads of administration and administrative staff regarding a series of results of archival implementation which will later be used as benchmarks for follow-up activities on improvements to archives management in increasing the quality of administrative services.